2022
DOI: 10.3390/en15134850
|View full text |Cite
|
Sign up to set email alerts
|

A New Reliability Allocation Method Based on PSA and AHP for Fusion Reactors

Abstract: Reasonable and feasible reliability index allocation is significant for improving safety and reducing costs for fusion reactors. Although the reliability index is allocated when designing some key systems, reliability allocation is not implemented from the overall layer to the system and component layers for fusion reactors. In this contribution, fusion reactors are divided into different layers by applying the Analytic Hierarchy Process (AHP); these layers include the overall layer, system layer and component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Therefore, an AHP-based prioritization tool was developed for radiological accident scenarios of NPPs [27]. A new reliability allocation method based on PSA (Probabilistic Safety Assessment) and AHP was designed for fusion reactors [28]. Another NPP-related study revealed that AHP is a potential input prioritization technique using Value Tree Analysis (VTA) with IRIDM [29].…”
Section: Contextual Backgroundmentioning
confidence: 99%
“…Therefore, an AHP-based prioritization tool was developed for radiological accident scenarios of NPPs [27]. A new reliability allocation method based on PSA (Probabilistic Safety Assessment) and AHP was designed for fusion reactors [28]. Another NPP-related study revealed that AHP is a potential input prioritization technique using Value Tree Analysis (VTA) with IRIDM [29].…”
Section: Contextual Backgroundmentioning
confidence: 99%